Action plan of zero unemployment destination - Mohamed Osman, Mariana; Abdul Rashid, Khairuddin; Shuid, Syafiee (2014)
One of the main socio-economic problems facing the nation at present is unemployment. Unemployment in Malaysia is becoming increasingly serious. The unemployment rate can be defined as the percentage of the labor force unemployed (McConnell & Brue, 2008). From the unemployment rate, it reflects how businesses are sustaining growth and creating jobs for people and pictured the consumers spending rate on goods and services. Snowdon and Vane (2005,p.1) expressed‘an economy that has successful macroeconomic management should experience low unemployment and inflation, and steady and sustained economic growth’s one of the macroeconomic variables,unemployment issues reflect how well an economy is using its resources (Andrei, Vasile and Adrian, 2009). Meanwhile, others see unemployment as one of the developmental problems (Akintoye, 2008) that measure the health of economy (Griffiths, 2007). Changes in unemployment depend mostly on inflows made up of non-employed people starting to look for jobs, of employed people who lose their jobs and look for new ones and of people who stop looking for employment. Overall, unemployment appears as a waste of scare resources. Thus, as one of key determinant in economy development, the study of unemployment is important. Through that, an active and positive result can be inserted into the governmental policy and direction to bring prosperous changes in economy development. A country’s unemployment rate tells more than just the percentage of the population that is without work. From the unemployment rate, it reflects how businesses are sustaining growth and creating jobs for people and pictured consumers are spending rate on goods and services. As increase in unemployment rate, people are inclined towards social-economic problems and life of crime. Subsequently, these phenomena will affect the economic growth.